A vocabulary of Philippine Food and Well-being - Sta. Maria, Felice (Budhi: a Journal of Ideas and Culture, 2018)
A preliminary study of culinary words during the Spanish colonial era reveals multiple dimensions to feeding. Entries in dictionaries of Philippine languages compiled from 1613 to 1895 reveal kalusugan as food for the body, kaginhawaan as sustenance for the soul, and the nayanaya as nutriment for the social self. The tripartite diet was a recipe for happiness and contentment. It is a legacy to review when designing contemporary strategies for national well-being.